THE INFLUENCE OF TAX REVENUE REALIZATION AND PLANNING ON TAX REVENUE TARGET ACHIEVEMENT WITH SERVICE QUALITY AS A MEDIATION VARIABLE AT THE REGIONAL REVENUE SERVICE UNIT (UPPD) BANJARMASIN II - M. Mirza Luffillah; Ibnu Al Saudi (Jurnal Ekonomi, 2023)
This study aims to examine the effect of tax revenue realization and planning on achieving the tax revenue target with service quality as a mediating variable at the Regional Revenue Service Unit (UPPD) Banjarmasin II. The population in this study is all people who pay taxes at the Banjarmasin II Regional Revenue Service Unit (UPPD) totaling 585 people, the data is taken from a questionnaire distributed to respondents. Data were analyzed using SmartPLS Version 3. The results of this study are Revenue Realization has a positive and significant effect on Service Quality, Tax Revenue Planning has a positive and significant effect on Service Quality, Revenue Realization has a positive and significant effect on Tax Revenue Target Achievement, Tax Revenue Planning has a positive and significant effect on Tax Revenue Target Achievement, Service Quality has a positive and significant effect on the Achievement of Tax Revenue Targets, Service Quality mediates the effect of Revenue Realization on Tax Revenue Target Achievement, Service Quality mediates the influence of Tax Revenue Planning on Tax Revenue Target Achievement